Policy-induced price distortions along the small ruminant value chains in Ethiopia - Kassie, Girma T.; Wubie, R.S.; Tokgoz, S.; Majeed, F.; Yitayih, Mulugeta; Rischkowsky, Barbara A. (Emerald Publishing Limited, 2019)
The purpose of this paper is to identify sources and quantifying distortions to agricultural incentives to produce along the small ruminant value chains in Ethiopia.National and district level average nominal rate of protection (NRPs) were computed for a five-year period (2010–2015). The authors developed four scenarios based on combinations of the different data generation processes employed in relation to each of the key variables.The NRPs at farm gate and retail market for both sheep and goats are negative indicating a strong deviation of producer and retailer prices from the comparable export prices over the five-year period. Policy induced distortions were separated from market inefficiencies through use of data on access costs throughout the value chain. These access costs are positive and significant in value. It is clear that market inefficiencies are also due to government policy to a certain extent.This study focuses only on sheep and goat value chains and covers only five-year period. This certainly limits the extrapolability of the results.This study presents the extent to which smallholder livestock keepers are discouraged through disincentives in a unique context. This is the first study done on small ruminant value chains in the developing world.